Length–weight and length–length relationships of 20 fish species from the upper Yangtze River, southwest China. (6th April 2017) - Xiong, F.; Liu, H. Y.; Duan, X. B.; Liu, S. P.; Chen, D. Q.
Summary: Length–weight (LWR) and length–length (LLR) relationships were estimated for 20 species of fish from the upper Yangtze River, southwest China. Samples were collected using multiple types of gear (2–6 cm mesh trammel nets, 2 cm mesh trap nets, and baited hooks) in Jiangjin and Yibin sections from 2007 to 2009. New maximum lengths for 16 species were recorded for FishBase. LWRs were significant for all species. Standard length–total length equations for converting size measurements for these 20 species are also presented. The results provide primary data for future fish research and conservation.